Screening of Phytochemicals, Antibacterial, Antioxidant and Anti-inflammatory Activity of Dictyota barteyresiana Seaweed Extracts - Durairaj, Swarna Bharathi; Andiyappan, Boopathy Raja (Asian Journal of Biological and Life Sciences, 2020)
To evaluate the antibacterial, antioxidant and anti-inflammatory activity of various extracts of Dictyota barteyresiana. Five strains of gram positive and gram negative bacteria such asProteus vulgaris,Pseudomonas aeruginosa,Bacillus subtilis,Staphylococcus aureusandKlebsiella pneumoniaecould be inhibited by plant extracts through disc diffusion method. The results were supported that antibacterial activity of ethanolic extract shows inhibition zone comparatively higher than other extracts. Antioxidant activity demonstrated in two various ways DPPH and Phosphomolybdenum assay from this ethanolic extract reduces free radical scavenging during tissue oxidation. Protein denaturation assay were performed for investigating anti-inflammatory method. Ethanol extract exhibits highest action over tissues which slightly best results than other samples. The present study is focused to establish the novel drugs from medicinal plant of Dictyota barteyresiana to get multiple characteristic features.
Keywords: Anti-inflammatory activity; Antibacterial activity; Antioxidant activity; Dictyota barteyresiana; Secondary metabolites